The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1186/s13578-016-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of long non-coding RNA H19 promotes P19CL6 cells proliferation and inhibits apoptosis during late-stage cardiac differentiation via miR-19b-modulated Sox6

Abstract: BackgroundRegulating cardiac differentiation to maintain normal heart development and function is very important. At present, biological functions of H19 in cardiac differentiation is not completely clear.MethodsTo explore the functional effect of H19 during cardiac differentiation. Expression levels of early cardiac-specific markers Nkx-2.5 and GATA4, cardiac contractile protein genes α-MHC and MLC-2v were determined by qRT-PCR and western lot. The levels of lncRNA H19 and miR-19b were detected by qRT-PCR. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…During the late stage of cardiac differentiation of P19CL6 cells, miR‐19b was negatively regulated by H19, as demonstrated by luciferase activity assay and qRT‐PCR. The overexpression of H19 significantly inhibited cell proliferation and promoted cell apoptosis via modulating miR‐19b and its target sox6, while the down‐regulation of H19 reversed these effects …”
Section: Lncrna As Mirna Sponges In Regulating the Biological Activitmentioning
confidence: 99%
See 2 more Smart Citations
“…During the late stage of cardiac differentiation of P19CL6 cells, miR‐19b was negatively regulated by H19, as demonstrated by luciferase activity assay and qRT‐PCR. The overexpression of H19 significantly inhibited cell proliferation and promoted cell apoptosis via modulating miR‐19b and its target sox6, while the down‐regulation of H19 reversed these effects …”
Section: Lncrna As Mirna Sponges In Regulating the Biological Activitmentioning
confidence: 99%
“…It has been gradually demonstrated that H19 may modulate a variety of cell biological functions by sequestering different miRNAs; H19 can serve as not only as a sponge of miRNAs, such as let‐7, miR‐103/107 and miR‐19b, in cell differentiation, necrosis and proliferation, but also as a precursor of miRNAs in the regulation of cardiomyocyte hypertrophy. The miR‐675 was validated to be located in the first exon of H19, and both H19 and miR‐675 were up‐regulated in hypertrophic heart tissue.…”
Section: Coexpression Of Lncrnas With Mirna In Modulating the Biologimentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides miR‐Function and ceRNA‐Function web tools to predict the function of ncRNAs (miRNAs, lncRNAs, pseduogenes) and protein‐coding genes from the miRNA‐mediated (ceRNA) regulatory networks . StarBase was commonly used in studying lncRNA‐miRNA‐mRNA network …”
Section: Methodsmentioning
confidence: 99%
“…Similar to these cardiac MHC isoforms, cardiac myosin light chain 2 (MLC-2v) is also transcribed during the course of differentiation [7]. When the 250 base pair (bp) promoter for the rat cardiac MLC-2v gene was connected upstream of the gene for green fluorescent protein (GFP) together with the enhancer portion of the cytomegalovirus (CMV) immediate early promoter, and the resulting reporter plasmid was stably introduced into P19CL6 cells, expression of GFP was limited to developing cardiac myocytes [8].…”
Section: Introductionmentioning
confidence: 99%